2017
DOI: 10.1590/s0004-2803.201700000-85
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Property of Fatigue Severity Scale and Correlation With Depression and Quality of Life in Cirrhotics

Abstract: -Background -Fatigue is a common complaint in cirrhotic patients and may be considered a debilitating symptom with negative impact on quality of life. Research on its etiology and treatment has been hampered by the lack of relevant and reproducible measures of fatigue. Objective -To evaluate the psychometric properties of the Fatigue Severity Scale (FSS) in cirrhotic patients and to correlate with depressive symptomatology and quality of life. Methods -Cross-sectional study with a convenience sample of 106 cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Multiple shared aetiologies between depression and fatigue have been proposed including systemic inflammation, mitochondrial dysfunction, oxidative stress, autoimmune abnormalities, hypothalamic-pituitary axis dysfunction, and structural and functional brain changes 41 , 42 . Strong associations between fatigue and depression have been found previously using the PedsQL-MFS 16 and the FSS (e.g., 43 ) although the original validation study emphasized its independence from depression 31 . Depression and fatigue are overlapping but distinct aspects of quality of life which are adversely affected by obesity, responsive to treatment, and important outcomes to consider in evaluating obesity intervention.…”
Section: Discussionmentioning
confidence: 85%
“…Multiple shared aetiologies between depression and fatigue have been proposed including systemic inflammation, mitochondrial dysfunction, oxidative stress, autoimmune abnormalities, hypothalamic-pituitary axis dysfunction, and structural and functional brain changes 41 , 42 . Strong associations between fatigue and depression have been found previously using the PedsQL-MFS 16 and the FSS (e.g., 43 ) although the original validation study emphasized its independence from depression 31 . Depression and fatigue are overlapping but distinct aspects of quality of life which are adversely affected by obesity, responsive to treatment, and important outcomes to consider in evaluating obesity intervention.…”
Section: Discussionmentioning
confidence: 85%
“…According to van den Berg-Emons et al (23) , this complaint remain for up to one year after liver transplantation. It is important to emphasize that fatigue can be difficult to measure and several questionnaires have been developed and tested in ESLD patients (3,15) . In this study we adopted the FSS, a validated fatigue scale known to provide reliable results in this setting (3) .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that fatigue can be difficult to measure and several questionnaires have been developed and tested in ESLD patients (3,15) . In this study we adopted the FSS, a validated fatigue scale known to provide reliable results in this setting (3) . The present study confirmed an inverse correlation of 6MST and FSS in this patient population, indicating that the higher the degree of fatigue, the lower the exercise test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[222] Fatigue has been associated with disease severity, ascites, encephalopathy, level of physical activity, poor sleep quality, decreased quality of life, mood disturbance, anxiety, depression, and job performance in cirrhosis and with age, sex, diet, mental status, and personality type in general populations. [220,[223][224][225][226][227][228] The evaluation of fatigue should include a comprehensive assessment of other potential contributing factors, such as hypothyroidism, depression, adrenal insufficiency, anemia, vitamin deficiency, and medication side effects (e.g., beta-blockers). [222,226,229,230] Nonpharmacological management of fatigue includes education, recommendations about energy-conserving and -restoring activities, and referral to physical and occupational therapy.…”
Section: Fatiguementioning
confidence: 99%